TECHNICAL NOTE A FAST DETERMINATION OF FE3+/FE2+ RATIO IN INDUSTRIAL MINERALS - Mulaba-Bafubiandi A.F.; Pollak H.; Mashlan M.; Jancik D.; Kholmetskii A. (My University, 2001)
Three-channels data collecting method for the determintion of Fe3+Fe2+ ratio in industrial iron-bearing minerals is proposed using Mössbauer effect spectroscopy. The method has been proved faster (less than five minutes) than the conventional collection of full Mössbauer spectra. Natural Ilmenite, Chromite and Stilpnomelane minerals can be used. The later is used to illustrate the method.